2020
DOI: 10.1002/anie.202006640
|View full text |Cite
|
Sign up to set email alerts
|

Heavy‐Atom Tunneling Through Crossing Potential Energy Surfaces: Cyclization of a Triplet 2‐Formylarylnitrene to a Singlet 2,1‐Benzisoxazole

Abstract: Not long ago, the occurrence of quantum mechanical tunneling (QMT) chemistry involving atoms heavier than hydrogen was considered unreasonable. Contributing to the shift of this paradigm, we present here the discovery of a new and distinct heavy‐atom QMT reaction. Triplet syn‐2‐formyl‐3‐fluorophenylnitrene, generated in argon matrices by UV‐irradiation of an azide precursor, was found to spontaneously cyclize to singlet 4‐fluoro‐2,1‐benzisoxazole. Monitoring the transformation by IR spectroscopy, temperature‐i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
76
2
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(86 citation statements)
references
References 60 publications
4
76
2
4
Order By: Relevance
“…[26][27][28] This has recently been confirmed by a set of studies of carbenes and nitrenes in matrix isolation at cryogenic temperatures. [29][30][31][32][33] Yet as we shall demonstrate, strong tunneling effects are not limited to such extreme environments but can also play a crucial role at room temperature in these nonadiabatic reactions and even allow for heavy-atom tunneling. Importantly, we find that the "corner cutting" effects first described in the context of adiabatic reactions 34 are much more important for nonadiabatic reactions and can drastically change the reaction mechanism.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…[26][27][28] This has recently been confirmed by a set of studies of carbenes and nitrenes in matrix isolation at cryogenic temperatures. [29][30][31][32][33] Yet as we shall demonstrate, strong tunneling effects are not limited to such extreme environments but can also play a crucial role at room temperature in these nonadiabatic reactions and even allow for heavy-atom tunneling. Importantly, we find that the "corner cutting" effects first described in the context of adiabatic reactions 34 are much more important for nonadiabatic reactions and can drastically change the reaction mechanism.…”
Section: Introductionmentioning
confidence: 69%
“…This explains the widely varying quality of results obtained with NA-TST/WC that can be found in the literature. 31,45,53,57 Instanton theory avoids these issues by locating the optimal reaction mechanism at each temperature/energy of interest in a fully ab initio manner. This has allowed us to unravel the substantial role of multidimensional quantum nuclear tunneling in this reaction, which proceeds by a corner-cutting pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They additionally found that this process is accompanied by tunnelling of hydrogen 41 or heavier atoms. 42,43 In order to simulate these nonadiabatic reactions, methods are required which go beyond the Born-Oppenheimer approximation.…”
Section: Introductionmentioning
confidence: 99%
“…The ring opening of 6 is particularly interesting since the resulting carbene 7 has a triplet ground state, and hence intersystem crossing (ISC) has to occur at some point along the reaction coordinate. [14][15][16] The lowest lying singlet state of carbene 7 is the open-shell (os) singlet state osS-7, which is predicted to be 8.4 kcal mol -1 above the triplet ground state T-7. The (planar) closed-shell singlet state csS-7 is with 26.1 kcal mol -1 at the CASPT2 level of theory much higher in energy.…”
Section: Introductionmentioning
confidence: 99%